Associations Between Serum 25‐Hydroxyvitamin D Concentrations and Multiple Health Conditions, Physical Performance Measures, Disability, and All‐Cause Mortality: The Concord Health and Ageing in Men Project. Issue 3 (27th February 2014) - Hirani, Vasant; Cumming, Robert G.; Naganathan, Vasi; Blyth, Fiona; Le Couteur, David G.; Handelsman, David J.; Waite, Louise M.; Seibel, Markus J.
<x xml:space="preserve">Abstract</x> Objectives To explore associations between serum 25‐hydroxyvitamin D (25(OH)D) levels and a wide range of health conditions, physical performance measures, disability, and mortality in a large epidemiological study to identify an optimum range for 25(OH)D concentrations. Design Cross‐sectional study, with additional prospective data on falls and mortality. Setting Concord Health and Ageing in Men Project, Sydney, Australia. Participants Community‐dwelling men aged 70 and older (N = 1, 659). Measurements Serum 25(OH)D levels, general health status, self‐reported diseases, physical performance measures, disability (activities of daily living and instrumental activities of daily living) and falls. Results Fair, poor, and very poor health; self‐reported diabetes mellitus; hyperglycemia; depression; muscle weakness; poor balance; and all‐cause mortality were all associated with serum 25(OH)D levels less than 50 nmol/L, even after adjustment for confounding. The findings also suggest that, in older men, for a wide range of health conditions, physical performance measures, disability, falls, and mortality, the optimum range of 25(OH)D is between 50.0 and 74.9 nmol/L, with no additional benefit for 25(OH)D levels of 75.0 nmol/L or greater. Conclusion Programs aimed at achieving an optimum range of serum 25(OH)D at levels between 50.0 and 74.9 nmol/L may have overall health benefits and such levels are adequate for older men.